A decade of institutional work: Context and opportunities for research - Zarpelon, Felipe; Faccin, Kadigia; Balestrin, Alsones; Bittencourt, Anelise Caon (Organizações & Sociedade, 2019)
The theoretical approach underlying institutional work sustains the understanding of the process through which individuals create, maintain and disrupt institutions. The interest in this approach encouraged the publication of a special issue in the journal Organization Studies in 2013. Lawrence, Leca, and Zilber introduced that special issue with an analysis of this field of study pointing to three avenues to further develop the theoretical approach: a) implementation of methodologies with an emphasis on the individual’s experiences; b) development of reflexivity by individuals; and c) commitment to practical contributions. We recall their research to revise the contributions of institutional work and to evaluate how these three avenues have been followed in this field of study. We then suggest an updated research agenda based on phenomena observed in the Brazilian context. Among the contributions of this study, we highlight a) the characteristics of the field of study on institutional work (state-of-the-art); b) central and adjacent themes to institutional work (map of themes); and c) opportunities and trends to further develop research on institutional work.